Article Commentary: Pediatric Palliative Care: A Reflection on Terminology. (January 2013) - Bergstraesser, Eva
The definition of palliative care is the cornerstone of a medical subspecialty that plays a particular role for all who need it, for all who practice it, and increasingly for those who try to understand it. The difficulties around the definition and terminology arise from problems in separating it from other concepts such as supportive care, constructs such as "palliative care is only about dying", or, in children, the rather vague use of terms like life-threatening and life-limiting diseases. These weaknesses have been recognized and important steps have been taken. This review discusses current definitions as well as efforts to overcome their weaknesses and make the term palliative care—for both children and adults—more intelligible.